2010
DOI: 10.1590/s1807-59322010000200015
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive methods in evaluation of inflammatory bowel disease: where do we stand now? An update

Abstract: The inflammatory bowel diseases, consisting of Crohn’s disease, ulcerative colitis and indeterminate colitis, are distinguished by idiopathic and chronic inflammation of the digestive tract. The distinction between inflammatory bowel diseases and functional bowel disorders, such as irritable bowel syndrome, can be complex because they often present with similar symptoms. Rapid and inexpensive noninvasive tests that are sensitive, specific and simple are needed to prevent patient discomfort, delay in diagnosis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…Compared to fecal biomarkers, serum biomarkers are nonspecific and less successful at indicating localized inflammation in the intestinal mucosa [27]. However, some serum biomarkers are more informative than others, especially for eliminating possible biological causes underlining IBS symptoms.…”
Section: Introduction/backgroundmentioning
confidence: 99%
“…Compared to fecal biomarkers, serum biomarkers are nonspecific and less successful at indicating localized inflammation in the intestinal mucosa [27]. However, some serum biomarkers are more informative than others, especially for eliminating possible biological causes underlining IBS symptoms.…”
Section: Introduction/backgroundmentioning
confidence: 99%
“…It is the major protein found in monocytes, macrophages and constitutes 50-60% of neutrophil cytosolic proteins (38,39). several studies have showed high fecal calprotectin levels are directly correlated with the quantification of the neutrophilic infiltrate in the gut mucosa as an indicator of infectious and inflammatory conditions (14,40).…”
Section: Resultsmentioning
confidence: 99%
“…It is an ironbiding glycoprotein with a molecular mass of about 80 kDa present in secondary (specific) granules especially in mature neutrophilic granulocytes [11,[12][13][14]. Although it provides an excellent quantifiable marker of neutrophilic inflammation, several exocrine cells also secrete lower amounts of this protein that are often present in lower concentrations in many fluids such as normal human milk, tears, synovial fluid, and serum.…”
Section: Lactoferrin (Lf)mentioning
confidence: 99%
“…Of course, FC assessment suffers from several limits as well. Any bleeding in the body over 100 ml, including menstrual bleeding, might increase calprotectin levels [30]. There are significant intraindividual biological variations, and acqueous feces may reduce the sensitivity of the rapid test [28,30].…”
Section: A Promising Fecal Marker In Dd: Fecal Calprotectinmentioning
confidence: 99%
“…Any bleeding in the body over 100 ml, including menstrual bleeding, might increase calprotectin levels [30]. There are significant intraindividual biological variations, and acqueous feces may reduce the sensitivity of the rapid test [28,30]. In some studies, low-dose aspirin did not increase the calprotectin levels, although the use of NSAIDs might cause an increase in calprotectin levels due to NSAIDs-induced enteropathy [31].…”
Section: A Promising Fecal Marker In Dd: Fecal Calprotectinmentioning
confidence: 99%